2021
DOI: 10.1186/s11671-021-03574-3
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Deformation Mechanism in Nano-cutting of Gallium Arsenide Using Molecular Dynamics Simulation

Abstract: During the nano-cutting process, monocrystalline gallium arsenide is faced with various surface/subsurface deformations and damages that significantly influence the product’s performance. In this paper, molecular dynamics simulations of nano-cutting on gallium arsenide are conducted to investigate the surface and subsurface deformation mechanism. Dislocations are found in the machined subsurface. Phase transformation and amorphization are studied by means of coordination numbers. Results reveal the existence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Additionally, we performed the crystal structure analysis and visualization using the open-source software OVITO, examined the surface morphology after atomic deposition, and calculated film surface parameters, such as crystal surface roughness and density, using code programming. Furthermore, we used the 'identify diamond structure' technique to analyze the structure types existing in the system and dislocation extraction algorithm (DXA) [40] to identify and calculate the dislocation lengths at different substrate temperatures.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…Additionally, we performed the crystal structure analysis and visualization using the open-source software OVITO, examined the surface morphology after atomic deposition, and calculated film surface parameters, such as crystal surface roughness and density, using code programming. Furthermore, we used the 'identify diamond structure' technique to analyze the structure types existing in the system and dislocation extraction algorithm (DXA) [40] to identify and calculate the dislocation lengths at different substrate temperatures.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…The study also confirmed that the anisotropy of the surface grain direction had an important influence on the scratching forces. Chen et al [ 35 ] employed molecular dynamics simulations to explore surface and subsurface deformations in gallium arsenide during nanocutting. Dislocations, phase transformations, and anisotropic effects were investigated, providing insights into performance-affecting factors in GaAs machining.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang 12 studied the process of single crystal copper cutting at the nanoscale, and found that at the same cutting speed, the cutting depth has a great influence on the subsurface dislocation form, and also has a very significant effect on the crystal structure type of the defect layer. Chen 13 used MD method to simulate the surface and subsurface deformation mechanism of gallium arsenide in the nano cutting process, and studied the influence of crystal anisotropy on the type and density of dislocations. Bai 14 simulated the subsurface damage of titanium alloy in machining process by using finite element method, and found that high internal stress will lead to the deformation of internal lattice, which resulted in the generation of micro cracks inside.…”
Section: Introductionmentioning
confidence: 99%